Empowering Saudi Women for Sports as Response to Saudi Vision 2030: An Analytical Study - Imawan, Riswanda; Zuliansyah, Zulmi; Surwandono, Surwandono (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
Saudi Arabia has undergone significant social and cultural transformations since it announced the ambitious Saudi Vision 2030, a plan to diversify the economy from oil dependence. One of the most impacted areas is sports, particularly women's sports. This article aims to examine the impact of Saudi Vision 2030 on women's empowerment in sports. This article uses a library research method and a descriptive analysis of literary sources from books, journals, and other secondary sources. This article also uses concepts of women empowerment and public diplomacy to explain the phenomena discussed in detail. The findings of this article show that Saudi Arabia's strategy of women's empowerment in sports has successfully promoted women's involvement in recreational and competitive sports. This article also concludes that sports have become a powerful tool for Saudi Arabia's public diplomacy efforts, projecting a new image of the country as one that upholds gender equality. The strategies implemented under Saudi Vision 2030 succeeded in empowering Saudi women in public and competition sports and contributed to a more inclusive and progressive society.